Thermoluminescence trap parameters of tailor-made Ge-doped optical fibre dosimeter - Al-mugren, K.S.; Shafiqah, A.S. Siti; Sani, S.F. Abdul; Tamchek, Nizam; Bradley, D.A. (Elsevier BV, 2024)
The feasibility study and thermoluminescence trap parameters of tailor-made Ge doped optical fibre as Thermoluminescence (TL) dosimeters has been investigated. The TL yield of the Ge-doped silica fibres produce are shown to be some 2.5× greater than that of the commercially available pure silica fibre Suprasil F300. Further, the pure silica fibre has been shown to provide a linear TL response, remaining so over the dose range 1–200 Gy, showing signs of saturation beyond 200 Gy. Conversely, the Ge-doped silica fibre is observed to show a linear response up to dose of 1000 Gy. For fading response, after 21 days, the signal loss, calculated with respect to the original value, was found to be some 13 % and 20 % for Ge-doped and pure silica, respectively. Based on the peak shape method of Chen (1969), the activation energy for de-trapping of electrons in the Ge-doped silica fibers has been shown to be 1.4× greater than that of the pure silica, with a frequency factor of 9.93 × 109 s−1. The results indicate the tailor- made Ge doped optical fibre to offer promising performance, providing both the greater activation energy and frequency factor compared to the situation for pure silica fiber.